Topical formulations containing Copaifera duckei Dwyer oleoresin improve cutaneous wound healing - Fernanda Dias; Lucas Pereira; Ricardo Furtado; Geórgia Modé Magalhães; Marina Miguel; Luis Gustavo Dias; Adriana Jorge; Cristiane Honsho; Sérgio Ambrósio; Jairo Bastos; Micaela Carrijo; Denise Tavares (Avicenna Journal of Phytomedicine, 2021)
Objective: Evaluation of the healing and toxicological effects of Copaifera duckei Dwyer oleoresin (CDO). Materials and Methods: Rodents with skin lesions were divided into nine groups, including daily treatments with 1, 3 and 10% CDO, collagenase, antibiotic ointment and control groups, for 14 days. Results: Treatment with 10% CDO reduced skin edema and hyperplasia, demonstrating anti-inflammatory effect of the oil. Reduction in the wound area was observed, indicating the healing effect of CDO. Histopathological analysis showed increases in angiogenesis and re-epithelialization in animals treated with the highest concentration. On the other hand, no alterations in ulcerations, inflammatory infiltrate, hemorrhage, congestion, degeneration, percentage of collagen fibers, number of cells stained with anti-macrophage migration inhibitory factor, or density of area stained with anti-collagen I and III were found. Toxicogenetic analysis revealed no differences in micronucleus frequencies or in the ratio of polychromatic erythrocytes to total erythrocytes between treated and negative control, demonstrating the absence of genotoxicity and cytotoxicity, respectively. There was no difference in levels of liver enzymes among groups, indicating the absence of hepatotoxicity. Conclusion: Formulations of CDO exerted beneficial effects on the stages of cutaneous wound healing and are promising options for the treatment of wounds.